Penelope Heynes at 80 m of Her World-record 100 m Race at the 1999 Pan Pacific Championships in Sydney - Rushall, B. S. (1999)
Video pictures (13 frames) and the appropriate technical/ biomechanical explanations for Penelope Heynes at 80 m of Her World-record 100 m Race at the 1999 Pan Pacific Championships in Sydney.